Optimalisasi Pengelolaan Koleksi Melalui Integrated Library System (INLISLite) untuk Meningkatkan Mutu Dinas Perpustakaan dan Kearsipan Kabupaten Jeneponto - Nur Fidia, Hikmah; Ramadayanti, Ramadayanti; Hidayah, Rahmi; Qoriyah, Nurul; Nurhalisa, Siti; Andriani, Nur (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
This article discusses the optimization of Internship Practice at the Library and Archives Office of Jeneponto Regency through the implementation of the Integrated Library System (Inlislite) to improve the quality of library collection management. Using a Service Learning approach, PKL students engaged in various activities, such as grouping, classification, shelving, barcode labeling, and data entry. This study aims to address technical and managerial challenges in managing library materials, including delays in collection input. The findings indicate that Inlislite enhances efficiency and modernizes library management systems, improves public services, and provides practical experience for students. Program evaluations highlight the successful implementation of each activity phase, contributing positively to students’ competency development and library quality. This article recommends strengthening coordination, conducting training, and developing Inlislite features to ensure sustainable library management while serving as a collaborative model between academics and practitioners.